A conceptual framework of web-based academic advisory information system - Ishak, Isma; Lehat, Mohd Lezam (2012)
Web-based academic advising system is gaining popularity in recent times among universities. Academicians are considering to introducing this for various benefits even though only few universities have web-based advising system at present. The aim of this paper is discover the main key areas requirements for web-based academic advisory system. The research uses a combination of approaches. Literature survey is conducted to investigate the current issues and common element of developing the web-based academic advising system. Finally a random survey is conducted to students and lecturers to gain their perspective on academic advising. The research resulted in proposed conceptual framework of web-based academic advising information system.